The vocation of man and the Great Commission: a theological dissertation based on the doctrine of reconciliation in Karl Barth's Church Dogmatics - Fourie, Ethne Maud (Rhodes University, Faculty of Divinity, Department of Divinity, 1976)
The purpose of this thesis is to establish a theological basis for an ecclesiology which takes account of the claim which the Lordship of Jesus Christ asserts over his appointed servants and the appropriate response from the Christian community corporately and from the members of the community individually. The interpretation and application of Christian discipleship by liturgical acts of the community in which the individual members participate and are prepared, trained and nourished for the purpose of equipping them for their corporate and individual task of witness is based on the promise and command of Jesus Christ recorded in Acts 1:8. The theological interpretation of the key concepts of the promise of power in the Holy Spirit and the commission to witness in the world is based on the theology of Karl Barth. Chapter I outlines the immediate context of the doctrine of vocation and the sending of the Christian community and the wider context of the doctrine of reconciliation and its place in the whole of theology. Chapters II and III enlarge on the vocation of man and the sending of the Christian community in the power of the Holy Spirit as the two parts of the doctrine of reconciliation which have particular relevance for our interpretation of the great commission. Chapter IV is devoted to a hypothesis of a special ethic based on Barth's unfinished work and Appendix A to methodological outline. Appendix B considers the practicality of this hypothesis in the light of two contemporary ecumenical interpretations and applications of the great commission. A concluding critique recognises the problems of the hypothesis and the inevitable problems that arise from any attempt to formulate a system or to define in precise categories the unique event of God's free and gracious love poured out and given to us in his Son, Jesus Christ our Lord.
Keywords: Barth, Karl, 1886-1968; Theology, Doctrinal; Great Commission (Bible); Reconciliation -- Biblical teaching